The moderating role of geopolitical fragmentation in energy transition-energy poverty: A cross distribution evidence from Europe - Yumeng Luo; Shajara Ul-Durar; Noman Arshed; Alireza Nazarian; Muhammad Shahbaz (Energy Policy, 2026)

Genome-wide identification, in-silico characterization, and expression analysis of polygalacturonases in different fungal species - Laiba Amin; Imran Zafar; Adil Jamal; Syed M. Safeer Mehdi Bokhari; Fayez Saeed Bahwerth; Muhammad Noman (Molecular Genetics and Genomics, 2026)

Analyzing integrated knowledge, attitudes and practices for the adoption of blast-resistant wheat varieties in Bangladesh: A structural equation modeling approach - Nasima Akter; Hasneen Jahan; Md Abdullah Al Noman; Md Monirul Islam; M. Wakilur Rahman; Sadika Haque; Pawan Kumar Singh; Muhammad Rezaul Kabir; Nanda Dulal Kundu (Crop Protection, 2026)

Multibiomarker assessment of greenly synthesized silver nanoparticles toxicity in the Tor putitora - Noman Waheed; Adeeba Naseer; Sabahat Saeed; Muhammad Fiaz Khan; Yukun Zhang; Venkata Siva Naga Sai Goli (Marine Pollution Bulletin, 2026)

Adsorption-coupled ozonation of real mariculture complex effluents' pharmaceuticals by lignocellulosic waste-based bimetallic biochar: Synergistic mechanism and implications - Muhammad Noman; Guangwei Yu; Wisal Ahmad; Wardah Hayat Khan (Journal of Water Process Engineering, 2026)

Coupled metabolomics and digital pathology to elucidate mechanistic pathways in earthworm (Eisenia fetida) exposed to environmentally relevant lithium - Noman Shakoor; Muhammad Adeel; Imran Azeem; Samama Tariq; Melanie Kah; Buana Suefo; Yukui Rui (Applied Soil Ecology, 2026)

Seedling Priming Enhances Selenium Assimilation During Agronomic Biofortification, Improving Selenium Concentration in Broccoli Florets: A Gene Expression Analysis - Everton Geraldo de Morais; Muhammad Noman; Pedro Antônio Namorato Benevenute; Antônio Chalfun-Júnior; Luiz Roberto Guimarães Guilherme (Journal of Plant Growth Regulation, 2026)
Selenium (Se) is beneficial for plants and essential for humans, yet it is typically present in the human diet only at trace levels. Agronomic biofortification offers a promising strategy to address this gap. Because Se and sulfur (S) share similar chemical properties and are taken up and assimilated through analogous pathways, sulfur-rich crops are particularly well-suited to Se biofortification. Broccoli, known for its naturally high S content, is therefore a strong candidate for this approach. Techniques such as the pre-application of elements at the seedling stage can modify plant metabolism (priming effect), enhancing their accumulation when the same element is reapplied at the adult stage. This study investigated how seedling priming with Se affects its uptake and assimilation during subsequent foliar biofortification, focusing on the expression of genes involved in the sulfur pathway. A greenhouse experiment was conducted in which broccoli plants were grown to floret production. Three days after the last foliar application, gene expression in the SULTR , APS , and APR families was quantified by RT-PCR, and Se concentration in florets was determined at harvest. Seedling priming was shown to create a more efficient metabolic apparatus, thereby increasing Se uptake by increasing the expression of SULTR1;1 . Following agronomic biofortification, seedling priming led to a significantly greater upregulation of genes involved in Se activation and reduction compared with non-primed plants. This was evidenced by a robust upregulation of APR1 (65-fold) and APS2 (+ 48%), which were directly associated with a marked increase in Se concentration in florets (+ 165%). Our findings suggest that seedling priming establishes a metabolic memory that improves Se assimilation when plants are later biofortified, making it an efficient strategy for agronomic biofortification.

An analysis of impact of soil co-pollution with lead and traditional/biodegradable microplastics on growth characteristics of maize (Zea mays L.) - Muhammad Kashif Irshad; Saba Saleem; Jamilur R. Ansari; Ali Noman; Muhammad Aqeel; Mohamed O. Alshahrani; Modhi O. Alotaibi; Muhammad Sohaib Irshad; Sang Soo Lee (Journal of Environmental Sciences, 2026)

Environmental KPI Reporting in Ports: Patterns, Gaps, and Opportunities for Systemic Change - Seyedeh Azadeh Alavi-Borazjani; Muhammad Noman Shafique; Zeeshan Arshad (International Journal of Environmental Research, 2026)
Ports play a critical role in global sustainability transitions, yet environmental performance reporting remains fragmented and uneven. This study examines environmental key performance indicator (KPI) reporting practices across twenty-five benchmark ports using a multi-category framework encompassing major environmental dimensions. The analysis reveals that, while most ports have established baseline transparency and compliance with international standards, reporting predominantly focuses on inventory-based and infrastructure-oriented indicators, with limited tracking of outcome-oriented performance metrics such as progress toward emissions reduction targets or reductions in stormwater pollution loads. Performance-based, outcome-oriented, and integrative KPIs remain underrepresented across environmental domains. High-level sustainability commitments are frequently disclosed without systematic progress tracking, and environmental domains are often reported in isolation, limiting holistic planning and comparability. Emerging areas such as climate risk assessment, environmental finance, acoustic management, and regenerative design exhibit particularly low reporting maturity. These findings underscore the need to shift from descriptive, compliance-driven disclosures toward harmonized, integrated KPI frameworks that support performance evaluation, strategic decision-making, and systemic sustainability transformation in the global port sector.

Seasonal fluctuations in the hypothalamic irisin and its correlation with the hypothalamic-pituitary-gonadal -axis activity in male rhesus monkeys (Macaca mulatta) - Muhammad Saqib; Amel Aftab; Ghulam Nabi; Muhammad Noman Khan; Hira Zubair; Fazal Wahab; Maha Abdullah Alwaili; Nawal Al-Hoshani; Muhammad Shahab (Journal of Comparative Physiology B, 2026)

Melatonin Buffers Microplastic-induced Oxidative Stress in Rice by Restoring Redox Balance, Antioxidants Reprogramming and Phytohormone Homeostasis - Ali Noman; Osman Sonmez; Noreen Khalid; Muhammad Kashif Irshad; Afrah E. Mohammed; Modhi O. Alotaibi; Muhammad Aqeel (Journal of Soil Science and Plant Nutrition, 2026)

Influence of Planting Density on Shoot Branching Regulated by Photosynthetic Activity and Hormonal Signaling in the Maize-Soybean Intercropping System - Irshan Ahmad; Jie Chen; Noman Shoaib; Sajad Hussain; Muhammad Arshad; Bin Cheng; Li Wang; Mei Xu; Yali Guo; Wenyan Wang; Yao Zhao; Weiguo Liu (Journal of Plant Growth Regulation, 2026)

Catalytic ozonation of P-nitrophenol in high chloride-containing wastewater with a Mn-Biochar-Kaolin Catalyst - Dinkayehu Tsegaye Awugichew; Muhammad Noman; Tekuma Abdisa Bakare; Kunthea Yun; Guangwei Yu (Journal of Water Process Engineering, 2026)

Circular valorization of agricultural, industrial, and post-consumer waste into fiber-reinforced composites for environmental sustainability - Muhammad Usman Shahid; Muhammad Noman Shahid; Zulfiqar Ahmad; Hafiz Muhammad Abdullah; Muhammad Muzammil Azad (Environmental Research, 2026)

A machine learning framework for evaluating cyclic resistance of sands with non-plastic fines - Arslan Mushtaq; Muhammad Salman; Muhammad Noman; Muhammad Faizan; Afaq Ahmed (Innovative Infrastructure Solutions, 2026)

Stomata-centered nanoguardians: revolutionizing plant pathogen defense - Muhammad Noman; Temoor Ahmed; Jorge L. Gardea-Torresdey; Fengming Song; Dongchang Sun; Jiaoyu Wang (Trends in Plant Science, 2026)

CRISPR-Cas9 and next-generation gene editing strategies for therapeutic intervention of neurodegenerative pathways in Alzheimer’s disease: a state-of-the-art review - Muhammad Sohail Khan; Imran Zafar; Adil Jamal; Fayez Saeed Bahwerth; Samiullah Khan; Muhammad Faizan; Hanif Khan; Muhammad Noman; Kendrix Okeibunor; Ashfaq Ahmad; Muhammad Zain Ul Abedin (Acta Neurologica Belgica, 2026)

Gastroprotective effect of Kahweol against ethanol-induced gastric ulcer by employing in silico, in vitro and in vivo approaches - Shahid Khan; Abdul Qadir; Jawad Azam; Muhammad Noman; Nadeem Ahmad; Zaheer Ul-Haq; Kashif Bashir; Tajamul Hussain; Salman Alrokayan; Muhammad Latif; Hussain Ali; Yousaf Kamal; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Improving Wheat Production in Pakistan Through an Economically Viable Solar‐Powered Rain Gun Sprinkler Irrigation System - Muhammad Asif; Shahzad Hussain Dahri; Bashir Ahmad; Noman Latif Sadozai; Sohail Raza Haidree; Abdul Hannan; Syed Qasim Ali Naqvi (Irrigation and Drainage, 2026)
In rainfed agriculture, limited water availability has become a challenging factor for sustainable farming and economic security. For regions with variable climate conditions, efficient water management practices must be adopted to improve livelihoods and food security. This study aimed to evaluate the role of supplemental irrigation for wheat crops in the Pothwar region. The irrigation management consists of I 0 (rainfed), I 1 (10 mm presowing), I 2 (10 mm at 50% soil moisture depletion [SMD]) and I 3 (25 mm at 75% SMD). The results revealed that, under I 3 , the grain yield increased by 49% and 17%, followed by I 2 (47% and 12%) compared to the rainfed yield of 1.85 and 3.93 tons/ha in Jand and NARC, respectively. The analysis of variance and Tukey's honestly significant difference (HSD) test revealed that the yield for I 0 value was significantly lower than that of all the irrigation treatments, while there were no significant differences among I 1 , I 2 and I 3 . The net benefit analysis revealed that I 3 was an economic irrigation schedule and paid back the total intervention cost by generating PKR 389,915/ha at NARC and PKR 283,915/ha at Jand in 3.83 and 4.93 years, respectively. This viable economic return makes solar‐powered irrigation systems reliable sources of water for water‐scarce and climate‐variable regions.

Synergistic effect of Clupea harengus by-product hydrolysates and kappa carrageenan mixture on oxidation prompted structural alterations in Clupea harengus proteins during frozen temperature variations - Noman Walayat; Piotr Kulawik; Asad Nawaz; Isam A. Mohamed Ahmed; Muhammad Faisal Manzoor; Zhucheng Su; Ran Wei (Food Hydrocolloids, 2026)

Advances in green food processing technologies: Enhancing efficiency, safety, and sustainability - Asad Nawaz; Sana Irshad; Xiaofang Luo; Noman Walayat; Putri Widyanti Harlina; Zuodong Qin; Muhammad Afzaal; Fakhar Islam (Food Control, 2026)

Synthesis of quinoline-pyridazinone hybrid molecules by using a bio-based aldo-X building block DMEMPO from levulinic acid - Muhammad Noman Haider Tariq; Gul Khanda Sajjad; Tianjian Zhang; Rongxian Bai; Babak Kaboudin; Yanlong Gu (Sustainable Chemistry and Pharmacy, 2026)

Advancing landslide knowledge and dissemination in Italy through IdroGEO 2.0 web platform - Alessandro Trigila; Carla Iadanza; Saverio Romeo; Gianluigi Di Paola; Piera Gambino; Stefano Calcaterra; Lena Rebecca Zastrow; Davide Romano; Tommaso Biondo; Muhammad Noman; Francesco Di Muro; Alessio Dragoni (Landslides, 2026)
Understanding landslide disaster risk, increasing public awareness, and improving monitoring technologies are key aspects that contribute, among others, to mitigating landslide risk, as also emphasized in the Kyoto (UN 2020) Commitment for Global Promotion of Understanding and Reducing Landslide Disaster Risk. To this end, the present technical note shows the recent development of the IdroGEO web platform as an innovative tool for landslide knowledge and dissemination in Italy. This improvement has been realized in response to both the new requests that emerged from users and the new requirements due to the extensive use of the platform itself. The platform, focused on landslides and floods and developed by ISPRA in 2020, has been upgraded to version 2.0 within the framework of the Geosciences IR project. The new version includes several enhancements, both in terms of new tools and data, aimed at improving the visualization and mapping of landslides, facilitating communication and dissemination of information, and allowing consultation of the National Register of in situ landslide monitoring systems. All the data and results obtained confirm that IdroGEO 2.0 serves as a key tool in landslide risk management strategy in Italy, supporting data collection, visualization, and dissemination. This is further evidenced by the growing public interest, with over 270,000 users accessing the platform and more than 14 million pages being viewed to date.

Classification of clay bricks using vision-based machine learning algorithms - Muhammad Faizan; Muhammad Salman; Muhammad Noman; Ali Akhtar; Afaq Ahmad; Matiullah Bakhtyar (Innovative Infrastructure Solutions, 2026)

Predicting fire resistance of reinforced concrete (RC) and concrete-filled steel tubular (CFST) columns through machine learning - Muhammad Noman; Muhammad Salman; Mati Ullah; Muhammad Faizan; Afaq Ahmed (Innovative Infrastructure Solutions, 2026)

Synergistic effects of biochar and silicon dioxide nanoparticles abate cadmium uptake and oxidative stress in tomato: Achieving crop resilience and environmental sustainability - Muhammad Kashif Irshad; Muhammad Waseem; Saba Saleem; Jamilur R. Ansari; Sana Ashraf; Wasim Javed; Ali Noman; Muhammad Aqeel; Muhammad Rizwan; Afrah E. Mohammed; Modhi O. Alotaibi; Muhammad Rizwan; et al. (Plant Science, 2026)

Protective effects of compound Gastrodia elata formula on the cognitive impairment induced by simulated weightlessness in mice - Fang Chen; Ning Jiang; Muhammad Noman Khan; Yiwen Zhang; Muhammad Zulqarnain Shakir; Guyue Zhou; Chenlu Xia; Yanfei Xu; Guanghua Lv; Mengzhou Xie; Xinmin Liu (Life Sciences in Space Research, 2026)

Chemical sensors for hazardous substances: advances in design, materials, and applications in environmental monitoring - Seyedeh Azadeh Alavi-Borazjani; Muhammad Noman Shafique (Environmental Monitoring and Assessment, 2025)

Sunlight-activated T6P precursor: a potent biostimulant for smart agriculture - Temoor Ahmed; Muhammad Noman; Yetong Qi; Jorge L. Gardea-Torresdey; Jason C. White; Xingjiang Qi (Trends in Plant Science, 2025)

Genome-wide identification and transcriptome-based expression analysis of hybrid sugarcane calmodulin-binding transcription activators under drought - Vitor Luciano Costa da Silva; Ana Maria Martinez; Maqsood Alam; Muhammad Noman; Antonio Chalfun-Junior (Plant Gene, 2025)

Predicting axial load capacity of CFRP fire-damaged RC columns through DANN - Muhammad Noman; Muhammad Yaqub; Muhammad Salman; Muhammad Faizan; Shakouri Mahmoudabadi; Afaq Ahmad (Innovative Infrastructure Solutions, 2025)
This paper presents the results of a deep neural network (DNN) model predicting the axial load-carrying capacity of fire-damaged concrete square and rectangular reinforced concrete columns subsequently repaired using carbon fiber-reinforced polymer (CFRP) composites. An experimental database comprising 143 column specimen samples was collected from the literature. Thirteen parameters were noted, including Length of Columns (mm), Width of Columns (mm), Corner Radius (mm), Height of Column (mm), Initial Compressive Strength of Concrete (MPa), Initial Tensile Strength of Steel (MPa), Longitudinal Reinforcement Ratio (As/Ag, %), Temperature of Fire (°C), Fire Exposure Time (Minutes), Number of Layers of CFRP(Count), Thickness of CFRP (mm), and Tensile Elastic Modulus of CFRP (GPa). These parameters served as inputs for the model, with the final axial compressive strength of the CFRP-repaired column considered as the target/output. DNN models were calibrated for numerous numbers of neurons in the hidden layers to achieve optimization. The proposed DNN model demonstrated strong agreement with the experimental database, exhibiting an overall correlation factor (R) of 0.99946. The predicted outcomes of the proposed model closely align with the experimental findings, as evidenced by a thorough comparison with prior experimental investigations. Consequently, this model holds potential value for engineers seeking speedy assistance in repairing fire-damaged structures using CFRP composites.

Enhancing Rice Water Productivity: Insights From Crop Water Needs and Irrigation in Pakistan - Ghani Akbar; Noman Latif Sadozai; Muhammad Ashraf (Irrigation and Drainage, 2025)
Excessive irrigation significantly reduces rice ( Oryza sativa L.) water productivity in Pakistan. This study evaluated crop water requirements, irrigation trends and water productivity across Pakistan's rice‐growing regions. Field data on crop yield, soil characteristics, irrigation practices and 10 years of weather data were collected from 11 districts across four provinces. The FAO AquaCrop model was used to assess crop water requirements (evapotranspiration, ET), the root zone water balance and water productivity. The crop water requirements ranged from 787 to 1151 mm, while irrigation consistently exceeded these needs by 95% to 123%. The irrigation water productivity (WPi) ranged from 0.09 to 0.19 kg/m 3 , and the evapotranspiration (ET) water productivity (WPet) ranged from 0.20 to 0.41 kg/m 3 . Excessive irrigation, 2 to 3 times the actual crop water needs, is attributed to traditional practices, a lack of knowledge and suboptimal irrigation schedules. Optimizing irrigation scheduling, adopting advanced technologies, and using high‐yielding, drought‐tolerant rice varieties could reduce water losses and improve crop yields. These findings offer actionable strategies to increase water productivity and ensure food security in Pakistan's rice‐growing regions, with potential applications in other water‐scarce, rice‐producing countries facing similar challenges.

Characterisation of the gut microbiome and surveillance of antibiotic resistance genes in green sea turtles (Chelonia mydas) - Dawood Ghafoor; Orachun Hayakijkosol; Noppadol Prasetsincharoen; Carla C.M. Chen; Muhammad Noman; Poommate Chomchat; Robert Kinobe (Marine Environmental Research, 2025)

Assessing the effect of a yeast product (Pichia guilliermondii) on growth performance, carcass traits, gut morphology, intestinal microbial computation, and immune response in broilers - Noman Khurshid; Saima Naveed; Fazal Raziq; Muhammad Tahir Khan; Assad Ullah (Tropical Animal Health and Production, 2025)

Airborne microplastics in leaves and food safety risks - Muhammad Ishfaq; Noman Shakoor; Matthias C. Rillig; Christoph-Martin Geilfus (Trends in Plant Science, 2025)

A novel approach towards green extraction of environmentally friendly anthraquinone based natural dye from amaltas fruits for leather coloration - Shahid Adeel; Fatima Batool; Tanvir Ahmad; Marwa Bashir; Noman Habib; Muhammad Imran; Rony Mia (Sustainable Chemistry and Pharmacy, 2025)

Magnetic biochar for the remediation of arsenic contaminated water: A complete guide of science, synthesis, and solutions - Yasir Hamid; Yonglong Chen; Muhammad Haris; Muhammad Usman; Bilal Hussain; Muhammad Saqib Rashid; Temoor Ahmed; Muhammad Noman; Xiaoe Yang (Journal of Environmental Chemical Engineering, 2025)

Immunomodulatory nano-biostimulants remodel transcriptome and metabolome for enhancing bayberry resilience against twig blight disease - Qi Zhang; Temoor Ahmed; Muhammad Noman; Yetong Qi; Munazza Ijaz; Zhitao Li; Han Yang; Li Sun; Xingjiang Qi; Bin Li; Shuwen Zhang (Chemical Engineering Journal, 2025)

Papaya leaf extract: A potential ally against dengue-induced thrombocytopenia in low-income countries- a mini review - Muhammad Noman Siddiqui; Ahmed Asad Raza; Aysha Asif; Abedin Samadi (Next Research, 2025)

Impact of Reconditioning Treatment at Different Temperatures on Potato Cultivars Stored Under Cold Conditions - Adnan Amjad; Aziz Mouhaddach; Hanane Latifi; Rabia Mehboob; Tusneem Kausar; Mohamed Bouhrim; Ramzi A. Mothana; Omar M. Noman; Farzana Siddique; Muhammad Bilal; Shehnshah Zafar; Ashiq Hussain (Potato Research, 2025)

Petrographic and geochemical analysis to predict the depositional setting of middle Eocene Jatta Gypsum, Kohat Sub-Basin, Pakistan - Noman Khan; Muhammad Kashif; Arzish Ithaf; Sheraz Habib; Hassanat Ullah; Khalid Ali Khan (Carbonates and Evaporites, 2025)

Contrasting photoperiods alter floral induction signaling and carbohydrate metabolism in sugarcane - Manoel Viana Linhares-Neto; Pedro Vitor Schumacher; Carlos Henrique Cardon; Debora Domiciano; Thales Henrique Cherubino Ribeiro; Murilo Fornari Junqueira Della Torre; Muhammad Noman; Joseph Colasanti; Antonio Chalfun-Junior (Theoretical and Experimental Plant Physiology, 2025)

Transforming cities from traditional to sustainability: role of electric vehicles and solar photovoltaic energy in decarbonization - Noman Sahito; Muhammad Yousif Mangi; Muhammad Aamir Basheer; Farrukh Baig; Zulfiqar Ali Lashari; Saima Kalwar (Environment, Development and Sustainability, 2025)

Association of microplastics with lead and cadmium in soil: Land-use and temporal trends - Noreen Khalid; Muhammad Aqeel; Shiou Yih Lee; Ujala Ejaz; Ali Noman; Muhammad Faisal Maqsood; Muhammad Kashif Irshad; Mohamed A. El-Sheikh (Journal of Environmental Chemical Engineering, 2025)

Techno-economic analysis and life cycle assessment of green hydrogen production: A case study of Sur Industrial City in Oman - Noman Raza Sial; Malik Sajawal Akhtar; Muhammad Islam; Muhammad Abdul Qyyum; Rashid Al-Abri; Ahmed Al-Hatrooshi; Ala’a H. Al Muhtaseb (Sustainable Cities and Society, 2025)

Mercury-induced alterations in soil microbiome: A potential for microbiome stewardship to remediate contaminated soils - Tao Lang; Muzammil Hussain; Muhammad Ishfaq; Noman Shakoor; Nora Fung-Yee Tam; Xiangyi Li; Min Pan; Zhengjie Zhu; Song Xin; Haichao Zhou (Journal of Cleaner Production, 2025)

Microplastic Contaminated Root Zone Supplementation With Ascorbic Acid Enhance Photosynthesis, Antioxidant Defense, ROS Scavenging, and Secondary Metabolites in Rice - Khairiah Mubarak Alwutayd; Muhammad Aqeel; Noreen Khalid; Saher Nawaz; Noreen Akhter; Muhammad Kashif Irshad; Uthman Bagith Algopishi; Suliman Mohammed Suliman Alghanem; Ali Noman (Journal of Soil Science and Plant Nutrition, 2025)

Nitric Oxide and Hydrogen Peroxide Coordinate to Improve Photosynthesis, Oxidative Defense, Osmoregulation, and Ions Homeostasis in Pea (Pisum sativum L.) Under Drought - Muhammad Kamran Afzal; Noman Habib; Muhammad Arslan Ashraf; Qasim Ali; Shafaqat Ali (Journal of Soil Science and Plant Nutrition, 2025)

A comprehensive review on the bioactivity and pharmacological attributes of Withania somnifera - Muhammad Usman Khalid; Muhammad Tauseef Sultan; Iqra Baig; Asad Abbas; Ahmad Mujtaba Noman; Abdellah Zinedine; Elena Bartkiene; João Miguel Rocha (Natural Product Research, 2025)

Non-leguminous green manures improve labile phosphorus availability and crop yield in agroecosystems: A global meta-analysis - Adnan Anwar Khan; Imran Azeem; Jing Hui; Yupei Chen; Yuqi Yuan; Tahir Shah; Muhammad Adeel; Noman Shakoor; Rana Muhammad Ammar Asghar; Weidong Cao; Dabin Zhang; Yajun Gao (Soil and Tillage Research, 2025)

Policy impacts of intellectual property and academic research trends in marine-derived collagen and chitin/chitosan value chains - Helena Vieira; Mariana Almeida; Muhammad Noman Shafique; Miguel C. Leal; Ana I. Lillebø (Marine Policy, 2025)

Chemically Degraded Soil: Strategies for Mitigating its Toxicity and Enhancing Sustainable Crop Production - Mavadat Hussain Alvi; Habib Ali; Kamran Haider; Adeel Hussain Chughtai; Muhammad Abdullah; Seema Batool; Shahid Rasool; Rana Noman Anwar; Sadam Hussain (Journal of Soil Science and Plant Nutrition, 2025)

Synthesis and application of kaolin-based catalyst for the degradation of ciprofloxacin in catalytic ozonation - Dinkayehu Tsegaye Awugichew; Guangwei Yu; Muhammad Noman; Ruqing Jiang; Kunthea Yun; Yanhui Chen (Journal of Water Process Engineering, 2025)

One step hydrothermal synthesis of green iron-modified catalyst by food waste digestate biogas residue for ozonation of ciprofloxacin: Characterization, degradation mechanism, DFT study and reactive oxygen species role - Muhammad Noman; Guangwei Yu; Ehiaghe Agbovhimen Elimian; Kunthea Yun (Journal of Environmental Chemical Engineering, 2025)

Bio-templating approach and DFT study of ZrMo@KIT-6 catalyst for the conversion of deep fried oil into sustainable biodiesel production - Muhammad Noman; Muhammad Farooq; Anita Ramli; Ghazala Abid; Fouzia Perveen; Dur Muhammad; Rida Ihsan; Faizan Jamil; Ali Raza Ayub; Noor Saeed khattak; Ata Ur Rahman (Fuel, 2025)

Bioinspired smart microcarriers precisely deliver agrochemicals in plants - Muhammad Noman; Temoor Ahmed; Jason C. White; Jiaoyu Wang (Trends in Plant Science, 2024)

Potential of iron oxide-modified biochar in simultaneous mitigation of lead and nickel toxicity in wheat (Triticum aestivum L.) - Tufail Shah; Muhammad Kashif Irshad; Wasim Javed; Mahshab Sheraz; Atif Muhmood; Ali Noman; Maryam M. Alomran; Sang Soo Lee; Jianying Shang (South African Journal of Botany, 2024)

Mechanistic insight into interactive effect of microplastics and arsenic on growth of rice (Oryza sativa L.) and soil health indicators - Muhammad Kashif Irshad; Muhammad Aqeel; Saba Saleem; Wasim Javed; Ali Noman; Min Woo Kang; Noreen Khalid; Sang Soo Lee (Science of The Total Environment, 2024)

Assessing the combined impacts of microplastics and nickel oxide nanomaterials on soybean growth and nitrogen fixation potential - Imran Azeem; Quanlong Wang; Muhammad Adeel; Noman Shakoor; Muhammad Zain; Adnan Anwar khan; Yuanbo Li; Kamran Azeem; Muhammad Nadeem; Guikai Zhu; Rui Yukui (Journal of Hazardous Materials, 2024)

Interactive effects of melatonin and salicylic acid on Brassica napus under drought condition - Noman Rafique; Noshin Ilyas; Muhammad Aqeel; Naveed Iqbal Raja; Ghulam Shabbir; Muhammad Ajaib; R. Z. Sayyed; Sulaiman Ali Alharbi; Mohammad Javed Ansari (Plant and Soil, 2024)

Correction: Cold atmospheric plasma-activated medium for potential ovarian cancer therapy - Shazia Tabassum; Muhammad Noman Khan; Nosheen Faiz; Almas; Bushra Yaseen; Iftikhar Ahmad (Molecular Biology Reports, 2024)

Cold atmospheric plasma-activated medium for potential ovarian cancer therapy - Shazia Tabassum; Muhammad Noman Khan; Nosheen Faiz; Almas; Bushra Yaseen; Iftikhar Ahmad (Molecular Biology Reports, 2024)

Correction: Examining Adaptive Responses of Foeniculum vulgare to Elevated Sodium and Chloride Stress in the Root Zone - Noreen Akhter; Rimsha Nafees; Ali Noman; Muhammad Aqeel; Naila Hadayat; Noreen Khalid; Abida Kausar; Mohammed O. Alshaharni; Muhammad Muslim Shahnaz; Arsal Saleem; Maryam M. Alomran (Journal of Soil Science and Plant Nutrition, 2024)

Examining Adaptive Responses of Foeniculum vulgare to Elevated Sodium and Chloride Stress in the Root Zone - Noreen Akhter; Rimsha Nafees; Ali Noman; Muhammad Aqeel; Naila Hadayat; Noreen Khalid; Abida Kausar; Mohammed O. Alshaharni; Muhammad Muslim Shahnaz; Arsal Saleem; Maryam M. Alomran (Journal of Soil Science and Plant Nutrition, 2024)

Ti3C2Tx-MXene based 2D/3D Ti3C2–TiO2–CuTiO3 heterostructure for enhanced pseudocapacitive performance - Muhammad Noman; Mirza Mahmood Baig; Qazi Muhammad Saqib; Swapnil R. Patil; Chandrashekhar S. Patil; Jungmin Kim; Youngbin Ko; Eunho Lee; Jinwoo Hwang; Seung Goo Lee; Jinho Bae (Chemical Engineering Journal, 2024)

Effects and fate of metal-based engineered nanomaterials in soil ecosystem: A review - Qibin WANG; Peng ZHANG; Weichen ZHAO; Shakoor NOMAN; Adeel MUHAMMAD; Guikai ZHU; Yi SUN; Quanlong WANG; Yaqi JIANG; Yukui RUI (Pedosphere, 2024)

Artificial intelligence and its role in developing predictive prognostic models for patients with aneurysmal subarachnoid hemorrhage: A systematic review - Muhammad Mohsin Khan; Noman Shah; Muhammad Mohsin Arshad; Talal Alrabayah; Sirajeddin Belkhair (Next Research, 2024)

Efficacy of Fe-Mg-bimetallic biochar in stabilization of multiple heavy metals-contaminated soil and attenuation of toxicity in spinach (Spinacia oleracea L.) - Muhammad Kashif Irshad; Jong Cheol Lee; Muhammad Aqeel; Wasim Javed; Ali Noman; Su Shiung Lam; Ali El Naggar; Nabeel Khan Niazi; Hun Ho Lee; Muhammad Ibrahim; Sang Soo Lee (Chemosphere, 2024)

Synthesis of surficial-modified green biochar catalyst generated by biogas residue biochar and potential application for catalytic ozonation degradation of ciprofloxacin - Muhammad Noman; Guangwei Yu; Dinkayehu Tsegaye Awugichew; Xinlin Li (Environmental Research, 2024)

Phytochemical profile, nutritional and medicinal value of Nigella sativa - Shabbir Hussain; Aqsa Rukhsar; Munawar Iqbal; Qurat ul Ain; Jahanzaib Fiaz; Noman Akhtar; Maria Afzal; Naveed Ahmad; Iqbal Ahmad; Wissem Mnif; Muhammad Hashir Khalid (Biocatalysis and Agricultural Biotechnology, 2024)

Quantum dots: next shift to combat plant diseases - Temoor Ahmed; Muhammad Noman; Jason C. White; Chuanxin Ma; Qi Wang; Bin Li (Trends in Plant Science, 2024)

Modulation of rhizosphere microbial community and metabolites by bio-functionalized nanoscale silicon oxide alleviates cadmium-induced phytotoxicity in bayberry plants - Temoor Ahmed; Linfei Shou; Junning Guo; Muhammad Noman; Yetong Qi; Yanlai Yao; Hafiza Ayesha Masood; Muhammad Rizwan; Md. Arshad Ali; Hayssam M. Ali; Bin Li; Xingjiang Qi (Science of The Total Environment, 2024)

Miniaturizing Power: Harnessing Micro-Supercapacitors for advanced micro-electronics - Qazi Muhammad Saqib; Abdul Mannan; Muhammad Noman; Mahesh Y. Chougale; Chandrashekhar S. Patil; Youngbin Ko; Jungmin Kim; Swapnil R. Patil; Muhammad Yousuf; Rayyan Ali Shaukat; Young Pyo Jeon; Deepak Dubal; et al. (Chemical Engineering Journal, 2024)

Correction: Taurine Enervates Nickel Stress in Lagenaria siceraria by Regulating Redox Balance, Methylglyoxal Detoxification, H2S Production, and Nickel Uptake - Arslan Hafeez; Rizwan Rasheed; Muhammad Rizwan; Noman Habib; Sadia Zafar; Mudassir Iqbal Shad; Shafaqat Ali; Muhammad Arslan Ashraf (Journal of Soil Science and Plant Nutrition, 2024)

Taurine Enervates Nickel Stress in Lagenaria siceraria by regulating Redox Balance, Methylglyoxal Detoxification, H2S Production, and Nickel Uptake - Arslan Hafeez; Rizwan Rasheed; Muhammad Rizwan; Noman Habib; Sadia Zafar; Mudassir Iqbal Shad; Shafaqat Ali; Muhammad Arslan Ashraf (Journal of Soil Science and Plant Nutrition, 2024)

Zinc oxide application alleviates arsenic-mediated oxidative stress via physio-biochemical mechanism in rice - Sanaullah Jalil; Muhammad Mudassir Nazir; Mohamed A. Eweda; Faisal Zulfiqar; Temoor Ahmed; Muhammad Noman; Muhammad A. U. Asad; Kadambot H. M. Siddique; Xiaoli Jin (Environmental Science and Pollution Research, 2024)

Cryptic footprint of thallium in soil-plant systems; A review - Noman Shakoor; Samama Tariq; Muhammad Adeel; Imran Azeem; Muhammad Nadeem; Muhammad Zain; Yuanbo Li; Wang Quanlong; Rabia Aslam; Yukui Rui (Chemosphere, 2024)

Unveiling the detrimental effects of polylactic acid microplastics on rice seedlings and soil health - Muhammad Kashif Irshad; Min Woo Kang; Muhammad Aqeel; Wasim Javed; Ali Noman; Noreen Khalid; Sang Soo Lee (Chemosphere, 2024)

Differential capacity of phragmites ecotypes in remediation of inorganic contaminants in coastal ecosystems: Implications for climate change - Noreen Akhter; Muhammad Aqeel; Shazia; Muhammad Kashif Irshad; Muhammad Muslim Shehnaz; Sang Soo Lee; Ali Noman; Asad Syed; A. Bokhari; Ali H. Bahkali; Ling Shing Wong (Environmental Research, 2024)

Technological advancements in water heating approaches for membrane distillation desalination process: From bulk to localized heating - Muhammad Usman Farid; Jehad A. Kharraz; Samriddhi Sharma; Rabia Jalil Khan; Noman Khalid Khanzada; Bhaskar Jyoti Deka; Manoj Kumar Nallapaneni; Shaurhat S. Chopra; Shao-Yuan Leu; Shadi W. Hasan; Nidal Hilal; Alicia K.J. An (Desalination, 2024)

Development of Maghemite Nanoparticles to Effectively Adsorb Methylene Blue Dye from Water - Muhammad Azeem Ashraf; Mumtaz Hasan Malik; Assad Farooq; Muhammad Tayyab Noman; Nayab Khan (Water, Air, & Soil Pollution, 2024)

Harnessing probiotics and prebiotics as eco-friendly solution for cleaner shrimp aquaculture production: A state of the art scientific consensus - Muhammad Noman; Syed Shabi Ul Hassan Kazmi; Hafiz Sohaib Ahmed Saqib; Usama Fiaz; Paolo Pastorino; Damià Barcelò; Muhammad Tayyab; Wenhua Liu; Zhen Wang; Zaher Mundher Yaseen (Science of The Total Environment, 2024)

Sustainable hydrogen production via microalgae: Technological advancements, economic indicators, environmental aspects, challenges, and policy implications - Hafiz Muhammad Uzair Ayub; Muhammad Nizami; Muhammad Abdul Qyyum; Noman Iqbal; Ala'a.H. Al-Muhtaseb; Mudassir Hasan (Environmental Research, 2024)

Metagenomic and biochemical analyses reveal the potential of silicon to alleviate arsenic toxicity in rice (Oryza sativa L.) - Temoor Ahmed; Junning Guo; Muhammad Noman; Luqiong Lv; Natasha Manzoor; Xingjiang Qi; Bin Li (Environmental Pollution, 2024)

Harnessing Melatonin Protective Efficacy in Capsicum Plants Against Nickel-Contaminated Soil - Maryam M. Alomran; Ali Noman; Noreen Khalid; Naila Hadayat; Fatmah M. Alqahtani; Fahad Mohammed Alzuaibr; Noreen Akhter; Mohamed Hashem; Talaat Habeeb; Omar Mahmoud Al-Zoubi; Muhammad Aqeel (Journal of Soil Science and Plant Nutrition, 2024)

Interplay between edaphic and climatic factors unravels plant and microbial diversity along an altitudinal gradient - Muhammad Aqeel; Noreen Khalid; Ali Noman; Jinzhi Ran; Abdul Manan; Qingqing Hou; Longwei Dong; Ying Sun; Yan Deng; Sang Soo Lee; Weigang Hu; Jianming Deng (Environmental Research, 2024)

Determination of microplastic pollution in marine ecosystems and its effective removal using an advanced nanobubble flotation technique - Jehad A. Kharraz; Mingyi Jia; Muhammad Usman Farid; Noman Khalid Khanzada; Nidal Hilal; Shadi W. Hasan; Alicia Kyoungjin An (Journal of Water Process Engineering, 2024)

Lithium-induced alterations in soybean nodulation and nitrogen fixation through multifunctional mechanisms - Noman Shakoor; Muzammil Hussain; Muhammad Adeel; Imran Azeem; Muhammad Arslan Ahmad; Muhammad Zain; Peng Zhang; Yuanbo Li; Wang Quanlong; Robert Horton; Yukui Rui (Science of The Total Environment, 2023)

Correction to: Genetic modification strategies for enhancing plant resilience to abiotic stresses in the context of climate change - Amman Khokhar; Muhammad Shahbaz; Muhammad Faisal Maqsood; Usman Zulfiqar; Nargis Naz; Usama Zafar Iqbal; Maheen Sara; Muhammad Aqeel; Noreen Khalid; Ali Noman; Faisal Zulfiqar; Khalid M. Al Syaad; et al. (Functional & Integrative Genomics, 2023)

National strategy for climate change adaptability: a case study of extreme climate-vulnerable countries - Noman Arshed; Muhammad Ibrahim Saeed; Sultan Salem; Uzma Hanif; Manzir Abbas (Environment, Development and Sustainability, 2023)

Dynamic interplay between nano-enabled agrochemicals and the plant-associated microbiome - Temoor Ahmed; Muhammad Noman; Jorge L. Gardea-Torresdey; Jason C. White; Bin Li (Trends in Plant Science, 2023)

Environmental implications of phosphate-based fertilizer industrial waste and its management practices - Noman Ahmad; Muhammad Usman; Hamaad Raza Ahmad; Muhammad Sabir; Zia Ur Rahman Farooqi; Muhammad Tahir Shehzad (Environmental Monitoring and Assessment, 2023)

Nexus between biomass energy, economic growth, and ecological footprints: empirical investigation from belt and road initiative economies - Muhammad Awais Anwar; Noman Arshed; Aviral Kumar Tiwari (Environmental Science and Pollution Research, 2023)

Microbe-oriented nanoparticles as phytomedicines for plant health management: An emerging paradigm to achieve global food security - Muhammad Noman; Temoor Ahmed; Usman Ijaz; Amir Hameed; Muhammad Shahid; Azizullah; Dayong Li; Fengming Song (Critical Reviews in Food Science and Nutrition, 2023)

Reverse osmosis membrane functionalized with aminated graphene oxide and polydopamine nanospheres plugging for enhanced NDMA rejection and anti-fouling performance - Noman Khalid Khanzada; Shazia Rehman; Jehad A. Kharraz; Muhammad Usman Farid; Muzamil Khatri; Nidal Hilal; Alicia Kyoungjin An (Chemosphere, 2023)

Molecular regulation of antioxidants and secondary metabolites act in conjunction to defend plants against pathogenic infection - Muhammad Usman Akbar; Muhammad Aqeel; Muhammad Shahzad Shah; Ghulam Jeelani; Naeem Iqbal; Ammara Latif; Rehab O. Elnour; Mohamed Hashem; Omar Mahmoud Alzoubi; Talaat Habeeb; Muhammad Qasim; Ali Noman (South African Journal of Botany, 2023)

Modifying engineered nanomaterials to produce next generation agents for environmental remediation - Muhammad Arslan Ahmad; Muhammad Adeel; Noman Shakoor; Rabia Javed; Muhammad Ishfaq; Yutao Peng; Muhammad Zain; Imran Azeem; Ilyas Ali; Muhammad Usman; Zihao Wu; Gholamreza Gohari; et al. (Science of The Total Environment, 2023)

Biogenic silicon nanoparticles mitigate cadmium (Cd) toxicity in rapeseed (Brassica napus L.) by modulating the cellular oxidative stress metabolism and reducing Cd translocation - Temoor Ahmed; Hafiza Ayesha Masood; Muhammad Noman; Arwa Abdulkreem AL-Huqail; Suliman MS Alghanem; Muhammad Munem Khan; Sher Muhammad; Natasha Manzoor; Muhammad Rizwan; Xingjiang Qi; Amany H.A. Abeed; Bin Li (Journal of Hazardous Materials, 2023)

Unveiling the potential of acidified cow dung in combination with plant growth promoting endophytes on growth, physiology, and yield improvement of maize in salt-affected soil - Muhammad Naveed; Rabail Zulekha; Khuram Shehzad Khan; Noman Younas; Muhammad Farhan Qadeer; Martin Brtnicky; Jiri Holatko; Adnan Mustafa (Arabian Journal of Geosciences, 2023)

Methanol production and purification via membrane-based technology: Recent advancements, challenges and the way forward - Kinza Qadeer; Amer Al-Hinai; Lai Fatt Chuah; Noman Raza Sial; Ala'a H. Al-Muhtaseb; Rashid Al-Abri; Muhammad Abdul Qyyum; Moonyong Lee (Chemosphere, 2023)

Microplastics in soil differentially interfere with nutritional aspects of chilli peppers - Khadiga Alharbi; Muhammad Aqeel; Noreen Khalid; Atia Nazir; Muhammad Kashif Irshad; Fahad Mohammed Alzuaibr; Haifa AbdulAziz Sakit AlHaithloul; Noreen Akhter; Omar Mahmoud Al-Zoubi; Muhammad Qasim; Khalid M.Al Syaad; Manal Abdullah AlShaqhaa; et al. (South African Journal of Botany, 2023)

Lipoic Acid Positively Regulates Tomato Growth and Yield by Improving Organic Osmolytes and Antioxidant Defense System Under Saline Conditions - Rohina Bashir; Hafiza Naila Ramzan; Saqib Mahmood; Muhammad Awais; Samina Hassan; Muhammad Aqeel; Haifa A. S. Alhaithloul; Tasahil S. Albishi; Sameer H. Qari; Ali Noman (Journal of Soil Science and Plant Nutrition, 2023)

Exogenous Application of Moringa Leaf Extract Confers Salinity Tolerance in Sunflower by Concerted Regulation of Antioxidants and Secondary Metabolites - Fozia Farhat; Nadra Ashaq; Ali Noman; Muhammad Aqeel; Shameem Raja; Rashda Naheed; Muhammad Faisal Maqsood; Ijaz Haider; Arneeb Tariq (Journal of Soil Science and Plant Nutrition, 2023)

Genetic modification strategies for enhancing plant resilience to abiotic stresses in the context of climate change - Amman KhokharVoytas; Muhammad Shahbaz; Muhammad Faisal Maqsood; Usman Zulfiqar; Nargis Naz; Usama Zafar Iqbal; Maheen Sara; Muhammad Aqeel; Noreen Khalid; Ali Noman; Faisal Zulfiqar; Khalid M. Al Syaad; et al. (Functional & Integrative Genomics, 2023)

Effects of Saccharomyces cerevisiae live cells and culture on growth and productive performance in lactating Nili-Ravi buffaloes - Mohsin Ali; Saeed Ahmed; Mubashar Ali; Nisar Ahmad; Mohammad Noman Tariq; Muhammad Usman; Ahmad Azeem Sardar (Tropical Animal Health and Production, 2023)

Unveiling the genomic potential of a novel thermostable glycoside hydrolases producing Neobacillus sedimentimangrovi UE25 - Uroosa Ejaz; Faizan Saleem; Rozina Rashid; Khwaja Ali Hasan; Muhammad Noman Syed; Muhammad Sohail (Antonie van Leeuwenhoek, 2023)

Recent progress on the heavy metals ameliorating potential of engineered nanomaterials in rice paddy: a comprehensive outlook on global food safety with nanotoxicitiy issues - Temoor Ahmed; Muhammad Noman; Muhammad Rizwan; Shafaqat Ali; Muhammad Shafiq Shahid; Bin Li (Critical Reviews in Food Science and Nutrition, 2023)

Transcriptomic and proteomic profiling reveals toxicity and molecular action mechanisms of bioengineered chitosan‑iron nanocomposites against Xanthomonas oryzae pv. oryzae - Temoor Ahmed; Luqiong Lv; Muhammad Noman; Hafiza Ayesha Masood; Muhammad Rizwan; Munazza Ijaz; Ashraf Atef Hatamleh; Munirah Abdullah Al-Dosary; Hayssam M. Ali; Jianping Chen; Bin Li (Pesticide Biochemistry and Physiology, 2023)

Sustainable environment quality: moderating role of renewable energy consumption in service sector for selected HDR listed countries - Mubasher Iqbal; Muhammad Shahid Hassan; Noman Arshed (Environmental Science and Pollution Research, 2023)

Glutathione treatment suppresses the adverse effects of microplastics in rice - Fu Chen; Muhammad Aqeel; Noreen Khalid; Muhammad Kashif Irshad; Fozia Farhat; Atia Nazir; Jing Ma; Muhammad Saeed Akhtar; Gaber E. Eldesoky; Ahmed Muteb Aljuwayid; Ali Noman (Chemosphere, 2023)

Salt ion mediated changes in biochemical and anatomical characteristics of Brassica napus can be countered with Moringa Leaf extract - Noreen Akhter; Aqsa Noreen; Saima Saifullah; Ali Noman; Muhammad Muslim Shahnaz; Puleng M. Letuma; Abida Kausar; Maham Siddique; Mohamed Hashem; Saad Alamri; Omar Mahmoud Al-zoubi; Muhammad Saleem; et al. (South African Journal of Botany, 2023)

Interactive effects of polystyrene microplastics and Pb on growth and phytochemicals in mung bean (Vigna radiata L.) - Fu Chen; Muhammad Aqeel; Noreen Khalid; Atia Nazir; Muhammad Kashif Irshad; Muhammad Usman Akbar; Fahad Mohammed Alzuaibr; Jing Ma; Ali Noman (Journal of Hazardous Materials, 2023)

Finite-time active fault-tolerant attitude control for flexible spacecraft with vibration suppression and anti-unwinding - Muhammad Noman Hasan; Muhammad Haris; Shiyin Qin (Advances in Space Research, 2023)

Effect of type and volume fraction of recycled-tire steel fiber on durability and mechanical properties of concrete - Babar Ali; Muhammad Ahmad Farooq; Rawaz Kurda; Rayed Alyousef; Muhammad Noman; Hisham Alabduljabbar (European Journal of Environmental and Civil Engineering, 2023)

Integrative Evaluation of the Ecological Hazards by Microplastics and Heavy Metals in Wetland Ecosystem - Shanza Zaka; Muhammad Aqeel; Adeel Mahmood; Ali Noman; Zarrin Fatima Rizvi; Wajiha Sarfraz; Aisha Nazir; Komal Arshad; Noreen Khalid (Bulletin of Environmental Contamination and Toxicology, 2023)

Projecting the excess mortality related to diurnal temperature range: A nationwide analysis in China - Jinlei Qi; Lili Chen; Peng Yin; Maigeng Zhou; Shushi Peng; Gang Liu; Lijun Wang; Muhammad Noman; Yang Xie; Zhaomin Dong; Yuming Guo (Science of The Total Environment, 2023)

Impact of plastic mulching as a major source of microplastics in agroecosystems - Noreen Khalid; Muhammad Aqeel; Ali Noman; Zarrin Fatima Rizvi (Journal of Hazardous Materials, 2023)

Calcium and L-glutamate present the opposite role in managing arsenic in barley - Fanrong Zeng; Muhammad Mudassir Nazir; Temoor Ahmed; Muhammad Noman; Shafaqat Ali; Muhammad Rizwan; Mohammad Shah Alam; Jonas Lwalaba Wa Lwalaba; Guoping Zhang (Environmental Pollution, 2023)

Iron-based nanomaterials reduce cadmium toxicity in rice (Oryza sativa L.) by modulating phytohormones, phytochelatin, cadmium transport genes and iron plaque formation - Pingfan Zhou; Peng Zhang; Mengke He; Yu Cao; Muhammad Adeel; Noman Shakoor; Yaqi Jiang; Weichen Zhao; Yuanbo Li; Mingshu Li; Imran Azeem; Like Jia; et al. (Environmental Pollution, 2023)

Antagonistic impact on cadmium stress in alfalfa supplemented with nano-zinc oxide and biochar via upregulating metal detoxification - Hafiz Abdul Kareem; Muhammad Adeel; Muhammad Azeem; Muhammad Arslan Ahmad; Noman Shakoor; Mahmood Ul Hassan; Sana Saleem; Annie Irshad; Junpeng Niu; Zhipeng Guo; Ćupina Branko; Roman Hołubowicz; et al. (Journal of Hazardous Materials, 2023)

An assessment of the efficacy of biochar and zero-valent iron nanoparticles in reducing lead toxicity in wheat (Triticum aestivum L.). - Muhammad Nauman Mahamood; Sihang Zhu; Ali Noman; Abid Mahmood; Sana Ashraf; Muhammad Aqeel; Muhammad Ibrahim; Sobia Ashraf; Rock Keey Liew; Su Shiung Lam; Muhammad Kashif Irshad (Environmental Pollution, 2023)

Microwave-assisted sustainable exploration of cocklebur leaves (Xanthium strumarium L.) as a novel source of distinct yellow natural colorant for dyeing cotton fabric - Muhammad Hussaan; Ahmad Raza; Noman Habib; Shahid Adeel; Naeem Iqbal; Muhammad Tariq Javed (Environmental Science and Pollution Research, 2023)

Ecological health risk assessment of microplastics and heavy metals in sediments, water, hydrophytes (Alternanthera philoxeroides, Typha latifolia, and Ipomoea carnea), and fish (Labeo rohita) in Marala wetlands in Sialkot, Pakistan - Komal Arshad; Muhammad Aqeel; Ali Noman; Atia Nazir; Adeel Mahmood; Zarrin Fatima Rizvi; Wajiha Sarfraz; Sajjad Hyder; Shanza Zaka; Noreen Khalid (Environmental Science and Pollution Research, 2023)

Nerium oleander could be used for sustainable management of traffic-borne elemental-enriched roadside soils - Noreen Khalid; Ali Noman; Atia Nazir; Aasma Tufail; Naila Hadayat; Fahad Mohammed Alzuaibr; Sobia Ikram; Noreen Akhter; Mumtaz Hussain; Muhammad Aqeel (Environmental Science and Pollution Research, 2023)

Interplay of higher plants with lithium pollution: Global trends, meta-analysis, and perspectives - Noman Shakoor; Muhammad Adeel; Imran Azeem; Muhammad Arslan Ahmad; Muhammad Zain; Aown Abbas; Muzammil Hussain; Yaqi Jiang; Pingfan Zhou; Yuanbo Li; Ming Xu; Yukui Rui (Chemosphere, 2023)

Environment relevant concentrations of lithium influence soybean development via metabolic reprogramming - Noman Shakoor; Muhammad Adeel; Muhammad Arslan Ahmad; Muzammil Hussain; Imran Azeem; Muhammad Zain; Pingfan Zhou; Yuanbo Li; Ming Xu; Yukui Rui (Journal of Hazardous Materials, 2023)

Assessment of wild turmeric–based eco-friendly yellow natural bio-colorant for dyeing of wool fabric - Noman Habib; Aamir Ali; Shahid Adeel; Fazal-ur-Rehman; Muhammad Aftab; Asma Inayat (Environmental Science and Pollution Research, 2023)

The nexus between environmental strategy and environmental performance: analyzing the roles of green product innovation and mechanistic/organic organizational structure - Noman Mustafa; Muhammad MansoorAsghar; Rozeia Mustafa; Zahoor Ahmed; Husam Rjoub; Rafael Alvarado (Environmental Science and Pollution Research, 2023)

Exploring antibiotic resistance genes, mobile gene elements, and virulence gene factors in an urban freshwater samples using metagenomic analysis - Sohail M. Noman; Muhammad Shafiq; Shabana Bibi; Bharti Mittal; Yumeng Yuan; Mi Zeng; Xin Li; Oluwaseyi Abraham Olawale; Xiaoyang Jiao; Muhammad Irshad (Environmental Science and Pollution Research, 2023)

Salinity mitigates cadmium-induced phytotoxicity in quinoa (Chenopodium quinoa Willd.) by limiting the Cd uptake and improved responses to oxidative stress: implications for phytoremediation - Noman Abdal; Ghulam Abbas; Saeed Ahmad Asad; Ayman A. Ghfar; Ghulam Mustafa Shah; Muhammad Rizwan; Shafaqat Ali; Muhammad Shahbaz (Environmental Geochemistry and Health, 2023)

Comparative Assessment of Remediation Potential of Xanthium strumarium Ecotypes in NaCl-Affected Root Zone - Noreen Akhter; Muhammad Aqeel; Muhammad Faisal Maqsood; Saher Nawaz; Muhammad Muslim Shahnaz; Noreen Khalid; Mohammed A. Basahi; Omar Mahmoud Al-Zoubi; Talaat Habeeb; Romina Alina Marc; Muhammad Kashif Irshad; Ali Noman (Water, Air, & Soil Pollution, 2022)

In Silico Dissection and Expression Analysis of Sucrose Synthase Gene Family in Sugarcane - Muhammad Noman; Iqra Siddique; Bilal Saleem; Saiqa Ilyas; Shaukat Ali; Muhammad Ramzan Khan (Sugar Tech, 2022)

Correction to: Interactive Effect of Boron Application Methods and Boron-Tolerant Bacteria (Bacillus sp. MN54) Improves Nodulation, Grain Yield, Profitability and Biofortification of kabuli Chickpea Grown Under Irrigated and Rainfed Conditions - Noman Mehboob; Tauqeer Ahmad Yasir; Sami Ul-Allah; Ahmad Nawaz; Muhammad Naveed; Mubshar Hussain (Journal of Soil Science and Plant Nutrition, 2022)

Agricultural Applications and Potential Risks of Copper-Based Nanoagrochemicals in Crop Cultivation - Yanwanjing Liu; Weichen Zhao; Yongguang Yin; Muhammad Adeel; Noman Shakoor; Yuanbo Li; Zhiqiang Tan; Yukui Rui; Qinghua Zhang; Jingfu Liu; Baoshan Xing (Reviews of Environmental Contamination and Toxicology, 2022)

Effects of two Mn-based nanomaterials on soybean antioxidant system and mineral element homeostasis - Yaqi Jiang; Pingfan Zhou; Tengtao Ma; Muhammad Adeel; Noman Shakoor; Yuanbo Li; Mingshu Li; Manlin Guo; Yukui Rui (Environmental Science and Pollution Research, 2022)

Antimicrobial activity of the biologically synthesized zinc oxide nanoparticles against important rice pathogens - Ayesha Iftikhar Cheema; Temoor Ahmed; Ali Abbas; Muhammad Noman; Muhammad Zubair; Muhammad Shahid (Physiology and Molecular Biology of Plants, 2022)

Environmental friendly pollution free bio-dyeing of wool with haar singhar (Coral Jasmine) flower extract - Shahid Adeel; Sehrish Ahmad; Noman Habib; Muhammad Jawwad Saif; Fatima Batool; Muhammad Aftab (Environmental Science and Pollution Research, 2022)

Mediation of Growth and Metabolism of Pisum sativum in Salt Stress Potentially Be Credited to Thiamine - Rashda Naheed; Maryeum Zahid; Muhammad Aqeel; Muhammad Faisal Maqsood; Hina Kanwal; Noreen Khalid; Mohamed Hashem; Saad Alamri; Ali Noman (Journal of Soil Science and Plant Nutrition, 2022)

Performance analysis of kinetic models in predicting asphaltene precipitation rate under different conditions of temperature and percentage of precipitant molecular weight - Syed Imran Ali; Shaine Mohammadali Lalji; Zahoor Awan; Saud Hashmi; Muhammad Noman; Nimra Yousaf (Arabian Journal of Geosciences, 2022)

Nexus between fossil fuel consumption and infant mortality rate: a non-linear analysis - Maqbool Hussain Sial; Noman Arshed; Muhammad Asif Amjad; Yousaf Ali Khan (Environmental Science and Pollution Research, 2022)

Facile synthesis of nanomaterials as nanofertilizers: a novel way for sustainable crop production - Farwa Basit; Sana Asghar; Temoor Ahmed; Usman Ijaz; Muhammad Noman; Jin Hu; Xinqiang Liang; Yajing Guan (Environmental Science and Pollution Research, 2022)

Structural, Biochemical, and Physiological Adjustments for Toxicity Management, Accumulation, and Remediation of Cadmium in Wetland Ecosystems by Typha domingensis Pers - Noreen Akhter; Omey Habiba; Mehwish Hina; Muhammad Muslim Shahnaz; Fahad Mohammed Alzuaibr; Saad Alamri; Mohamed Hashem; Noreen Khalid; Muhammad Aqeel; Ali Noman (Water, Air, & Soil Pollution, 2022)

Feeding niche overlap between native and alien fishes in Swat River, Khyber Pakhtunkhwa, Pakistan - Amir Said; Muhammad Imran; Muhammad Tahir Waseem; Abdul Majid Khan; Noman Khalique; Ghulam Sarwar; Rana Manzoor Ahmad (Environmental Biology of Fishes, 2022)

Ecofriendly application of coconut coir (Cocos nucifera) extract for silk dyeing - Shahid Adeel; Shumaila Kiran; Muhammad Shahid; Sajid Raza Habib; Noman Habib; Muhammad Hussaan (Environmental Science and Pollution Research, 2022)

Inducible knockdown of Mycobacterium smegmatis MSMEG_2975 (glyoxalase II) affected bacterial growth, antibiotic susceptibility, biofilm, and transcriptome - Muhammad Haris; Changming Chen; Jing Wu; Muhammad Noman Ramzan; Ayaz Taj; Shanshan Sha; Hayan Ullah; Yufang Ma (Archives of Microbiology, 2022)

Seed Priming with Sodium Nitroprusside and H2O2 Confers Better Yield in Wheat Under Salinity: Water Relations, Antioxidative Defense Mechanism and Ion Homeostasis - Noman Habib; Qasim Ali; Shafaqat Ali; Muhammad Zulqarnain Haider; Muhammad Tariq Javed; Mubashra Khalid; Rashida Perveen; Abdulaziz Abdullah Alsahli; Mohammed Nasser Alyemeni (Journal of Plant Growth Regulation, 2021)

Ameliorative mechanisms of turmeric-extracted curcumin on arsenic (As)-induced biochemical alterations, oxidative damage, and impaired organ functions in rats - Anam Ishaq; Huma Gulzar; Ali Hassan; Muhammad Kamran; Muhammad Riaz; Aasma Parveen; Muhammad Sohaib Chattha; Noman Walayat; Sana Fatima; Sobia Afzal; Shah Fahad (Environmental Science and Pollution Research, 2021)

Phyto-derivatives: an efficient eco-friendly way to manage Trogoderma granarium (Everts) (Coleoptera: Dermestidae) - Waqar Islam; Ali Noman; Komivi Senyo Akutse; Muhammad Qasim; Habib Ali; Ijaz Haider; Mohamed Hashem; Saad Alamri; Omar Mahmoud al Zoubi; Khalid Ali Khan (International Journal of Tropical Insect Science, 2021)

Correction to: Elucidating the distinct interactive impact of cadmium and nickel on growth, photosynthesis, metal-homeostasis, and yield responses of mung bean (Vigna radiata L.) varieties - Muhammad Aqeel; Noreen Khalid; Aasma Tufail; Rana Zaheer Ahmad; Muhammad Salim Akhter; Muhammad Luqman; Muhammad Tariq Javed; Muhammad Kashif Irshad; Saad Alamri; Mohamed Hashem; Ali Noman (Environmental Science and Pollution Research, 2021)

Distribution-based effects of disaggregated GDP and environmental quality—a case of quantile on quantile estimates - Muhammad Shahid Hassan; Mubasher Iqbal; Noman Arshed (Environmental Science and Pollution Research, 2021)

Elucidating the distinct interactive impact of cadmium and nickel on growth, photosynthesis, metal-homeostasis, and yield responses of mung bean (Vigna radiata L.) varieties - Muhammad Aqeel; Noreen Khalid; Aasma Tufail; Rana Zaheer Ahmad; Muhammad Salim Akhter; Muhammad Luqman; Muhammad Tariq Javed; Muhammad Kashif Irshad; Saad Alamri; Mohamed Hashem; Ali Noman (Environmental Science and Pollution Research, 2021)

Late Cretaceous pelagic laminites at the northwestern margin of Indian plate, Pakistan: implications for basin bathymetry and ophiolite emplacement - Sajjad Ahmad; Suleman Khan; Bilal Wadood; Asad Naseer; Muhammad Noman; Jamal Wadood; Muhammad Muslim (Carbonates and Evaporites, 2021)

A blessing in disguise?: Assessing the impact of 2010–2011 floods on trust in Pakistan* - Noman Ahmad; Muhammad Zeeshan Younas (Environmental Science and Pollution Research, 2021)

Physiological homeostasis for ecological success of Typha (Typha domingensis Pers.) populations in saline soils - Noreen Akhter; Muhammad Aqeel; Muhammad Muslim Shahnaz; Ghalia S. H. Alnusairi; Suliman Mohammed Alghanem; Abida Kousar; Mohamed Hashem; Hina Kanwal; Saad Alamri; Aisha Ilyas; Omar Mahmoud Al-zoubi; Ali Noman (Physiology and Molecular Biology of Plants, 2021)

Rising Metals Concentration in the Environment: A Response to Effluents of Leather Industries in Sialkot - Noreen Khalid; Zarrin Fatima Rizvi; Nousheen Yousaf; Shujaul Mulk Khan; Ali Noman; Muhammad Aqeel; Komal Latif; Asmara Rafique (Bulletin of Environmental Contamination and Toxicology, 2021)

Managing organic carbon of sandy clay loam soil with organic amendments to promote particle aggregation - Haroon Shahzad; Muhammad Iqbal; Noman Latif; Muhammad Arshad Khan; Qudrat Ullah Khan (Arabian Journal of Geosciences, 2021)

Identification and computational analysis of USH1C, and SLC26A4 variants in Pakistani families with prelingual hearing loss - Muhammad Noman; Shazia A. Bukhari; Sakina Rehman; Muhammad Qasim; Muhammad Ali; Saima Riazuddin; Zubair M. Ahmed (Molecular Biology Reports, 2020)

Optimizing Boron Seed Coating Level and Boron-Tolerant Bacteria for Improving Yield and Biofortification of Chickpea - Mubshar Hussain; Noman Mehboob; Muhammad Naveed; Kousar Shehzadi; Tauqeer Ahmad Yasir (Journal of Soil Science and Plant Nutrition, 2020)

24-Epibrassinolide Alleviates the Injurious Effects of Cr(VI) Toxicity in Tomato Plants: Insights into Growth, Physio-Biochemical Attributes, Antioxidant Activity and Regulation of Ascorbate–Glutathione and Glyoxalase Cycles - Sumira Jan; Ali Noman; Cengiz Kaya; Muhammad Ashraf; Mohammed Nasser Alyemeni; Parvaiz Ahmad (Journal of Plant Growth Regulation, 2020)

Bioaccumulation of ytterbium oxide nanoparticles insinuate oxidative stress, inflammatory, and pathological lesions in ICR mice - Muhammad Adeel; Jin Tingting; Tariq Hussain; Xiao He; Muhammad Arslan Ahmad; Muhammad Kashif Irshad; Noman Shakoor; Peng Zhang; Xie Changjian; Yi Hao; Zhang Zhiyong; Rabia Javed; et al. (Environmental Science and Pollution Research, 2020)

Assessment of antibiotics use for children upper respiratory tract infections: a retrospective, cross-sectional study from Pakistan - Zia Ul Mustafa; Muhammad Salman; Alina Zeeshan Rao; Noman Asif; Sanan Amjad Butt; Naureen Shehzadi; Khalid Hussain (Infectious Diseases, 2020)

Achromobacter sp. FB-14 harboring ACC deaminase activity augmented rice growth by upregulating the expression of stress-responsive CIPK genes under salinity stress - Muhammad Shahid; Asad Ali Shah; Farwa Basit; Muhammad Noman; Muhammad Zubair; Temoor Ahmed; Tahir Naqqash; Irfan Manzoor; Awais Maqsood (Brazilian Journal of Microbiology, 2020)

Competitiveness, governance and globalization: What matters for poverty alleviation? - Muhammad Shahid Hassan; Samra Bukhari; Noman Arshed (Environment, Development and Sustainability, 2020)

The effect of lead pollution on nutrient solution pH and concomitant changes in plant physiology of two contrasting Solanum melongena L. cultivars - Muhammad Tariq Javed; Noman Habib; Muhammad Sohail Akram; Qasim Ali; Muhammad Zulqurnain Haider; Kashif Tanwir; Asia Shauket; Hassan Javed Chaudhary (Environmental Science and Pollution Research, 2019)

Hepatitis E outbreak in the province of Punjab, Pakistan: a call for action - Muhammad Salman; Zia Ul Mustafa; Noman Asif (Infectious Diseases, 2019)

Assessment of flood-induced changes in soil heavy metal and nutrient status in Rajanpur, Pakistan - Farhan Hafeez; Noman Zafar; Rashid Nazir; Hafiz Muhammad Rashad Javeed; Muhammad Rizwan; Faridullah; Saeed Ahmad Asad; Akhtar Iqbal (Environmental Monitoring and Assessment, 2019)

Synthesis and applications of nano-TiO2: a review - Muhammad Tayyab Noman; Muhammad Azeem Ashraf; Azam Ali (Environmental Science and Pollution Research, 2019)

Effects of road proximity on heavy metal concentrations in soils and common roadside plants in Southern California - Noreen Khalid; Mumtaz Hussain; Hillary S. Young; Benjamin Boyce; Muhammad Aqeel; Ali Noman (Environmental Science and Pollution Research, 2018)

Sugar beet extract acts as a natural bio-stimulant for physio-biochemical attributes in water stressed wheat (Triticum aestivum L.) - Ali Noman; Qasim Ali; Jazia Naseem; M. Tariq Javed; Hina Kanwal; Waqar Islam; Muhammad Aqeel; Noreen Khalid; Sara Zafar; Muhammad Tayyeb; Naeem Iqbal; Mahmooda Buriro; et al. (Acta Physiologiae Plantarum, 2018)

Biodegradation of plastics: current scenario and future prospects for environmental safety - Temoor Ahmed; Muhammad Shahid; Farrukh Azeem; Ijaz Rasul; Asad Ali Shah; Muhammad Noman; Amir Hameed; Natasha Manzoor; Irfan Manzoor; Sher Muhammad (Environmental Science and Pollution Research, 2018)

Deciphering the growth, organic acid exudations, and ionic homeostasis of Amaranthus viridis L. and Portulaca oleracea L. under lead chloride stress - Muhammad Tariq Javed; Muhammad Sohail Akram; Noman Habib; Kashif Tanwir; Qasim Ali; Nabeel Khan Niazi; Huma Gul; Naeem Iqbal (Environmental Science and Pollution Research, 2018)

Basic leucine zipper domain transcription factors: the vanguards in plant immunity - Ali Noman; Zhiqin Liu; Muhammad Aqeel; Madiha Zainab; Muhammad Ifnan Khan; Ansar Hussain; Muhammad Furqan Ashraf; Xia Li; Yahong Weng; Shuilin He (Biotechnology Letters, 2017)

Petrography, provenance, diaganesis and depositional environment of Murree Formation in Jhelum Valley, Sub Himalayas, Azad Jammu and Kashmir, Pakistan - Muhammad Zaheer; Muhammad Sabir Khan; Muhammad Saleem Mughal; Noman Abbasi (Arabian Journal of Geosciences, 2017)

Proteomic approach to address low seed germination in Cyclobalnopsis gilva - Madiha Zaynab; Sonia Kanwal; Muhammad Furqan; Waqar Islam; Ali Noman; Ghulam Muhammad Ali; Nazia Rehman; Sara Zafar; Kalsoom Sughra; Muhammad Jahanzab (Biotechnology Letters, 2017)

miRNAs: Major modulators for crop growth and development under abiotic stresses - Ali Noman; Shah Fahad; Muhammad Aqeel; Usman Ali; Amanullah; Sumera Anwar; Shahbaz Khan Baloch; Madiha Zainab (Biotechnology Letters, 2017)

miRNA-based heavy metal homeostasis and plant growth - Ali Noman; Muhammad Aqeel (Environmental Science and Pollution Research, 2017)

Correlation of Cadmium and Magnesium in the Blood and Serum Samples of Smokers and Non-Smokers Chronic Leukemia Patients - Noman Khan; Hasan Imran Afridi; Tasneem Gul Kazi; Muhammad Balal Arain; Muhammad Bilal; Asma Akhtar; Mustafa Khan (Biological Trace Element Research, 2017)

Chromium Exposure in the Adult Population, Consuming Different Types of Smokeless Tobacco Products in Pakistan - Asma Akhtar; Hasan Imran Afridi; Tasneem Gul Kazi; Farah Naz Talpur; Sadaf Sadia Arain; Jameel Ahmed Baig; Noman Khan; Mustafa Khan; Muhammad Bilal (Biological Trace Element Research, 2017)

Vortex-assisted ionic liquid-based dispersive liquid–liquid microextraction for assessment of chromium species in artificial saliva extract of different chewing tobacco products - Asma Akhtar; Tasneem Gul Kazi; Hassan Imran Afridi; Syed Ghulam Musharraf; Farah Naz Talpur; Noman Khan; Muhammad Bilal; Mustafa Khan (Environmental Science and Pollution Research, 2016)

Drought tolerance potential of Vigna mungo L. lines as deciphered by modulated growth, antioxidant defense, and nutrient acquisition patterns - Qasim Ali; Muhammad Zulqurnain Haider; Wasif Iftikhar; Sidra Jamil; M. Tariq Javed; Ali Noman; Muhammad Iqbal; Rashida Perveen (Brazilian Journal of Botany, 2016)

Purification and Characterization of Novel α-Amylase from Bacillus subtilis KIBGE HAS - Saeeda Bano; Shah Ali Ul Qader; Afsheen Aman; Muhammad Noman Syed; Abid Azhar (AAPS PharmSciTech, 2011)